Parental involvement in the development of children’s organizational skills - YÜKSEL, MÜGE (My University, 2022)
This study aims to explore mothers’ perceptions regarding their contributions to their 9- to 12-year-old children’s organizational skills (e.g., time management, material organization, self-care skills). This mixed-methods study implements the explanatory sequential design. In the first stage, the mothers (n = 191) filled out the Questionnaire for Assessing Students’ Organizational Abilities (QASOA) and answered some demographic questions online. Based on the results from the QASOA, children with deficits in their organizational skills have been distinguished from those who do not have deficits. In the second stage, five mothers with children showing no deficit in organizational skills and five mothers with children showing deficits in these skills were interviewed on their involvement in their children’s organizational skills. The qualitative data were analyzed using directed content analysis. The findings suggest ways mothers, teachers, and psychological counselors can contribute to developing children’s organizational skills.

Bu çalışma, annelerin, 9-12 yaş arası çocuklarının organizasyonel becerilerine (zaman yönetimi, materyal organizasyonu, öz-bakım becerileri) yaptıkları katkıları incelemeyi amaçlamaktadır. Araştırmada, açımlayıcı sıralı karma desen yöntemi kullanılmıştır. Anneler (n=191), ilk aşamada, çevrim içi anket yoluyla Öğrencinin Organizasyonel Becerilerini Değerlendirme Anketi (ÖOBDA)’ni doldurmuş ve bazı demografik soruları yanıtlamışlardır. ÖOBDA sonuçlarına göre organizasyonel becerilerinde problem olan çocuklar, organizasyonel becerilerinde problem olmayanlardan ayrılmıştır. İkinci aşamada, organizasyonel becerilerinde problem olan ve olmayan beşer çocuğun anneleriyle, çocuklarının organizasyonel becerilerine katılımlarına dair sorular içeren bir görüşme yapılmıştır. Nitel veriler yönlendirilmiş içerik analizi kullanılarak analiz edilmiştir. Sonuçlar, annelerin, öğretmenlerin ve psikolojik danışmanların çocukların organizasyonel becerilerinin gelişimine nasıl katkıda bulunabileceğine dair öneriler sunmaktadır.
Çocukların organizasyonel becerilerinin gelişiminde ebeveyn katılımı
Keywords: Organizational Skills; Parental Involvement; Qualitative Research; Mixed Methods; Organizasyonel Beceriler; Ebeveyn Katılımı; Nitel Araştırma; Karma Yöntem